Measuring the Effect of Income Inequality, Financial Inclusion, Investment, and Unemployment, on Economic Growth in Africa: A Moderating Role of Digital Financial Technology - Nambie, Nicholas Bamegne; Dadzie, Philomena; Haywood-Dadzie, Dorcas Oye (International Journal of Economics and Financial Issues, 2023)
The significance of understanding the effect of income inequality, financial inclusion, investment, unemployment on economic growth in Africa is imperative in academic literature, and contributes meaningfully to policy decision making. All the variables in the study play important roles in economic growth. This paper, therefore empirically analyses the contribution of income inequality, financial inclusion, investment, unemployment, on economic growth using secondary data spanning 2001 to 2022. Two-step system generalized method of moments (GMM) estimator is used to analyse the data extracted from the world development indicators (WDI). It was revealed that, income inequality and unemployment have a significant negative relationship with economic growth whilst financial inclusion and investment also have a significant positive relationship with economic growth. Also, financial technology, which is the moderator variable has significant relationship with economic growth. It was concluded that, policy makers should ensure equitable distribution of wealth, stabilize the economy, develop the skills of young entrepreneurs, and invest in financial technology to enhance economic growth in Africa.